Citalopram and escitalopram plasma drug and metabolite concentrations: genome‐wide associations. (August 2014) - Ji, Yuan; Schaid, Daniel J.; Desta, Zeruesenay; Kubo, Michiaki; Batzler, Anthony J.; Snyder, Karen; Mushiroda, Taisei; Kamatani, Naoyuki; Ogburn, Evan; Hall‐Flavin, Daniel; Flockhart, David; Nakamura, Yusuke; et al.
<x xml:space="preserve">Abstract</x> Aims Citalopram (CT) and escitalopram (S‐CT) are among the most widely prescribed selective serotonin reuptake inhibitors used to treat major depressive disorder (MDD). We applied a genome‐wide association study to identify genetic factors that contribute to variation in plasma concentrations of CT or S‐CT and their metabolites in MDD patients treated with CT or S‐CT. Methods Our genome‐wide association study was performed using samples from 435 MDD patients. Linear mixed models were used to account for within‐subject correlations of longitudinal measures of plasma drug/metabolite concentrations (4 and 8 weeks after the initiation of drug therapy), and single‐nucleotide polymorphisms (SNPs) were modelled as additive allelic effects. Results Genome‐wide significant associations were observed for S‐CT concentration with SNPs in or near the CYP2C19 gene on chromosome 10 (rs1074145, P = 4.1 × 10−9) and with S‐didesmethylcitalopram concentration for SNPs near the CYP2D6 locus on chromosome 22 (rs1065852, P = 2.0 × 10−16), supporting the important role of these cytochrome P450 (CYP) enzymes in biotransformation of citalopram. After adjustment for the effect of CYP2C19 functional alleles, the analyses also identified novel loci that will require future replication and functional validation. Conclusions In vitro and in vivo studies have suggested that the biotransformation of CT to monodesmethylcitalopram and didesmethylcitalopram is mediated by CYP isozymes. The results of our genome‐wide association study performed in MDD patients treated with CT or S‐CT have confirmed those observations but also identified novel genomic loci that might play a role in variation in plasma levels of CT or its metabolites during the treatment of MDD patients with these selective serotonin reuptake inhibitors.